INFLUENCE OF ORGANIZATIONAL ENVIRONMENT ON EMPLOYEE PERFORMANCE STUDY IN THE GOVERNMENT OF THE DISTRICT CITY - Christina, Veronica; S. Brahmana, Sunardi; R. , Adjeng Mariana (International Journal of Psychosocial Rehabilitation, 2020)
Knowledge of the influence of the organizational environment, in the form of internal control and leadership style on employee performance is the aim of this study. A district has a regional government agency called the regional secretariat, which works to organize the government. This regional government agency apparently showed that the performance of its employees was not yet effective. Effective employee performance in addition to being caused by internal factors, known as the individual characteristics of each employee can also be caused by external factors, namely the organizational environment. Organizational environmental factors that are suspected of causing ineffective employee performance include internal control and leadership style. The study population was employees who worked at the Kuningan Regency regional secretariat. The sample in this study was 116 employees with purposive sampling. Data processing uses multiple regressions whose results indicate that employee performance can be influenced by the organizational environment in the form of internal control and leadership style